The metastatic niche in the liver: tilling the soil for pancreatic cancer progression - Hann, Alexander; Sainz Jr, Bruno; Hermann, Patrick C. (Translational Cancer Research, 2017)
Despite new developments in adjuvant and palliative treatment, pancreatic ductal adenocarcinoma (PDAC) still has a very poor prognosis. One of the main factors that prevent surgical resection of the tumor in curative intent is metastasis at the time of diagnosis. This perspective article summarizes new insights on the influence of premalignant lesions and PDAC itself on the formation of the metastatic niche in the liver.